Examining the influence of satisfaction and regret on online shoppers' post-purchase behaviour. Issue 6 (24th December 2020) - Tata, Sai Vijay; Prashar, Sanjeev; Parsad, Chandan
Abstract : Purpose: The present research has used the expectancy–confirmation model along with the regret theory to examine the influence of six e-retailers' characteristics and confirmation on shoppers' satisfaction or regret. Further, the effect of these two cognitive constructs has been investigated on consumers' post-purchase behaviour like the intention to write reviews, repurchase intentions and brand-switching behaviour. Design/methodology/approach: Extensive review of the literature was undertaken to identify the related factors. Data were collected using the survey instrument from 367 respondents. Structural equation modelling using Amos 22.0 was carried out for analysing the data. Findings: The findings from the data collected from 367 respondents include the significant influence of price transparency, service quality and firms' sincerity on shoppers' satisfaction. Originality/value: Contrary to expectations, it is observed that product assortment, product quality and quality of personalisation did not have any such influence. Also, a firm's sincerity is the only factor that influenced regret. The noticeable outcome of the study pertains to the fact that online reviews are only provided by satisfied shoppers and not shoppers who regret. Rather, such regretting customers prefer switching to the alternative brand(s) and are less inclined to repurchase.